Efficacy of a novel surgical approach: sutureless correction of conjunctivochalasis using new conjunctival forceps combined with high-frequency electrocautery - Song, Tingting; Liang, Xianjun; Lin, Yingjie; Luo, Huihui (Frontiers in Ophthalmology, 2025)
PurposeTo investigate the efficiency, efficacy, and safety of application new conjunctival forceps combined with high-frequency electrocautery-assisted for treatment of conjunctivochalasis (Cch).MethodsThis study included data from 19 patients (22 eyes)with conjunctivochalasis who underwent treatment from January to December 2023. Cch correction was performed with our new conjunctival forceps (Patent Number: ZL 2022 2 0320601.0), which offers enhanced precision and stability in grasping the conjunctiva, combined with high-frequency electrocautery (Ellman, America) for sutureless correction. Surgical duration was recorded. Cch severity, assessed with lip-parallel conjunctival folds (LIPCOF), along with discomfort scored by Ocular Surface Disease Index (OSDI), were compared pre- and post-operatively. A reduction in LIPCOF grade and complete healing of the conjunctival epithelium post-surgery within one month were considered successful outcomes. Healing and potential complications were checked at one week and one month.ResultsThe mean surgical duration was 6.9 ± 1.5 minutes. Significant improvement in LIPCOF grades was observed over time (χ²=62.824, p<0.01), with 59.1% of eyes achieving grade 0 at 1 week postoperatively, increasing to 95.5% at 1 month. OSDI scores showed no difference between preoperative (38.54) and 1-week postoperative (41.67) values (p=0.922), but significantly decreased by 1 month (16.67, p<0.001). Complete healing was noted at electrode contact sites by 1 week, while incisions managed with novel conjunctival forceps showed 75% healing rate; all incisions were fully healed by 1 month. Mild postoperative congestion and edema resolved completely without major complications.ConclusionThe new conjunctival forceps with high-frequency electrocautery for sutureless Cch correction proved to be efficient, effective, and safe.